片麻痺を対象とした家庭用手指リハビリテーション機器における手指運動機能の自動評価 - 千葉, 馨; 石田, 裕二; 古館, 裕大; 三上, 貞芳 (ライフサポート, 2021)
A home medical supporting technology is quite required in aging society in Japan. The robotics technology can contribute to home medical field. The rehabilitation of the hemiplegia by using a rehabilitation supporting robot exists as one of the fields robotics technology can contribute to. Hemiplegia has the character which the paralysis of finger is difficult to recover. Due to this tendency, a patient must rehabilitate after discharge. However, a patient cannot rehabilitate at home because most devices such as exoskeleton type and glove type tend to be high cost. In this study, we develop finger rehabilitation device for a patient who leaves a hospital, aiming at low cost, simple mechanism, ease to introduce to home. In this paper, we describe the automated evaluation system of motor function of finger by using the finger rehabilitation device. The device requires the pinch task and grasp task. During the task, all finger movements are measured by pressure sensors as time-series signal. After measuring, the feature of motor function is extracted by calculating the dissimilarity with health subject’s signal. As a result, we can show that the feature corresponds to the recovery of the paralysis and the automated evaluation system is realized.